Risk factors of drug-resistant epilepsy in children under three-year-old - Sukmono, Suryawati; Mangunatmadja, Irawan; Pardede, Sudung O. (Paediatrica Indonesiana, 2025)
Background Repeated seizures may result in chronic injury to the brain, triggering the neuroplasticity process that can cause or augment existing pathological processes. High neuroplasticity during first 3 year of life may influence the clinical course and outcome of children with epilepsy. Objective To evaluate initial risk factors and evolution risk factors during treatment to predict drug-resistant epilepsy in children under 3 years old. Initial risk factors consist of initial seizure frequency, seizure type, imaging result, history of febrile convulsion, neurodevelopmental status and initial electroencephalography (EEG) result. Evolution risk factors evaluate changes in initial risk factors and seizure control after treatment. Evolution risk factors consist of early response to therapy (seizure control during the first 6 months of treatment), evolution of seizure type and frequency, changes in EEG (background rhythm and epileptiform discharges) during treatment and neurodevelopmental evolution. Methods This retrospective cohort study used medical record data of pediatric patients 1 month to 3 years old with drug-resistant epilepsy seeking treatment at Cipto Mangunkusumo Hospital, Anakku Clinic Pondok Pinang, and National Brain Center Hospital, Jakarta, from 2015 to 2020. Results Thirty-three subjects met drug-resistant epilepsy criteria. Abnormal EEG was the only initial risk factor significantly associated with drug-resistant epilepsy (OR 4.48; 95%CI 1.82 to 11.03; P=0.001). Increased seizure frequency (aOR 7.0; 95%CI 1.0 to 49.7; P=0.048) and seizure persistence during the first six months of treatment (aOR 10.92; 95%CI 2.6 to 45.87; P=0.01) were significantly related with drug-resistant epilepsy. Conclusion Abnormal initial EEG result was the only initial risk factor associated with drug-resistant epilepsy. Evolution risk factors associated with drug-resistant epilepsy were increased seizure frequency and seizure persistence in the first six months of treatment.